PENGEMBANGAN BROWNIES KUKUS TEPUNG TALAS-KECAMBAH KACANG HIJAU DAN UBI UNGU KUKUS (TALAHIBU) UNTUK IBU HAMIL KURANG ENERGI KRONIK (KEK) - Islamiati Putri Amalia; Hery Winarsi; Gumintang Ratna Ramadhan (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Background: The prevalence of pregnant women with a risk of Chronic Energy Deficiency (CED) is quite high (24.2%). CED in pregnant women requires additional feeding interventions (PMT). Brownies enriched with taro flour–mung bean sprouts and purple sweet potato (TALAHIBU) were chosen as it is an energy-dense product and expected to have preferred organoleptic value and energy as PMT. Objectives: To determine the phenolic antioxidant content of the best TALAHIBU formula and to determine the serving size of TALAHIBU. Methodology: This factorial experimental study used a randomized block design (RBD) with 2 factors, consisting of taro flour-mung bean sprout proportion and the percentage of added fine steamed sweet potato. Organoleptic variable analysis used Friedman test continued with 5% Multiple Appeal Test. The best treatment combination was chosen, continued with Proximate and phenolic test then energy calculations. Results: The best treatment was TALAHIBU G2J2 with water content of 23.94% BW; ash content 3.16% bb; fat 25.7% BW; carbohydrates 45.57% bb; protein 1.63% bb; energy 419.83kcal; and phenolic antioxidant 19,1 mg/g. Conclusion: The best product TALAHIBU is suitable PMT for pregnant women with CED by serving 5 slice brownies per day.